Evaluation of a dual-purpose chemical applicator for paddy fields - Abubakar, Mohammed Shu'aibu; Ahmad, Desa; Othman, Jamarei; Sulaiman, Shamsuddin; Misron, Norhisam (Science Publications, 2011)
Problem statement: One of the major problems of rice production is the shortage of labor resulting from migration from rural to urban areas, making it very difficult to meet peak demands for paddy production. In most developing countries of Southeast Asia, agricultural mechanization of paddy field operation is mostly carried out using conventional machines. For example in rice production powerintensive operations such as water pumping, land preparations, transplanting seedlings, harvestings and threshing are being mechanized but other operations like fertilizer and chemical (pesticides) applications are not yet fully mechanized, rather they are performed manually with motorized backpack knapsack sprayers which have many disadvantages. The main objective of this study was to develop and evaluate a new concept dual-purpose chemical applicator for paddy fields farmers in order to complement the labor shortage during the peak period. Approach: A dual-purpose chemical applicator for flooded paddy field was evaluated using the S341.4 Standard in respect to the distribution patterns/droplet sizes and uniformity of spreading/spraying for the chemical application to boost agricultural mechanization in rice production and also to overcome the safety concern of hazardous spray drift during chemical application by the paddy farmers. The dual purpose applicator was mounted on a high clearance prime mover. The machine performances for both granular and liquid chemical application were reported. Results: Results for urea granular chemical indicate that at low (40 kg ha-1) and high (120 kg ha-1) rates and 550 rpm disc speed distribution pattern skewed to the left whereas the distribution pattern shape at medium (80 kg ha-1) rates was good flattop. At high rate (120 kg ha-1) and 1000 rpm disc speed, mean distribution pattern became poor (M-shape) and also at low and medium application rates the distribution pattern shapes lopsided to the left. For NASA glyphosate liquid chemical herbicide, the average values of (VDM) and (NMD) were 108 and 79 µm at 80 lt/ha application rate and 5000 rpm rotary disc speed and 185 and 119 µm at 80 lt/ha application rate 3000 rpm rotary disc speed. Conclusion: The experimental results from the experimental tests suggest that the average effective field capacity for the equipment with a prime mover was found to be 0.89 ha h-1 or 7.12 ha/man-day for an 8 h working day.